Generic Competency for the Acknowledgement and Appreciation for Human Diversity: Evaluation of Professors’ Initial Training - Paz-Delgado, Carla Leticia (2017)
Currently, teaching takes place in highly diverse social, educational and cultural environments. Understanding and accepting this fact has allowed that pre-service and in-service teaching training be taught as education for diversity. It is in this sense that the Universidad Pedagógica Nacional Francisco Morazán (UPNFM, Pedagogical University Francisco Morazán) has, in a recent curricular reform, included a generic and transverse competency to contribute to the training of the University faculty, so that they can appreciate and understand diversity as an enriching asset of the educational process. The main objective of this research is to identify the level of development of this competency to propose a strategy to visualize inclusive education as transverse knowledge. This project was developed from the perspective of research for improvement and decision making, using a mixed methodology and collecting data through the analysis of documents, in-depth interviews, and a questionnaire. The participants in the study were 225 students, who were in their professional internship II, and eight professors from the General Ed courses.The results showed that UPNFM, in its curricular offer, has achieved great improvements as for the training of their faculty members regarding attention to diversity by incorporating in its curriculum a competency linked to an inclusive education. However, both members of the faculty and students pointed out that they did not have the skills to apply teaching strategies suitable to deal with diversity. Therefore, it is necessary to strengthen the process of curricular implementation through ongoing training of university professors.